Design of biogas pipeline - Energy and sanitation - Godoy, E.; Camargo, J. R.; Santos, R. R.; Rezende, F. S.; Cassula, A. Matotta; Trindade, E. Marques; Danieletto, J. R. Bertoncello (Trans Tech Publications, 2013)
The study aimed at developing a methodology for the design and appropriate use of materials in the pipes for the collection and distribution of biogas. The increasing use of biogas for distributed generation in agro-industries, sewage treatment effluent and anaerobic landfills, and the absence of a specific standard for biogas pipes led to the development of the work. Because there is no standard for design and delivery of pipes for the collection and distribution of biogas, the main eco-efficient energy projects implemented in the country, units digester / bike generator 50 kVA to 200 kVA, were used duct poly vinyl chloride (PVC) that permeable to gases, suffers from contamination of biogas network to air, leaks, reduce the efficiency of filter retention of H2S and reduced life of the motor generator. The methane in biogas reacts with PVC and decomposition occurs, dissolution, swelling and loss of ductility of the tube. Since polyethylene is the material world-known and most suitable for transportation of gas fuels, and the fact that its raw material, ethylene in the chain of thermoplastics derived from petroleum, polyethylene comes before the PVC, which makes it more economical and safe. © (2013) Trans Tech Publications, Switzerland.
Keywords: Biogas; Biogas pipeline; Design; Agroindustries; Energy project; Motor generator; Vinyl chlorides; Chlorine compounds; Diffusion in solids; Distributed power generation; Ethylene; Materials handling; Methane; Petroleum transportation; Pipelines; Polyethylenes; Polyvinyl chlorides; Sewage treatment